Triterpene glycosides and phenylpropane derivatives from Staurogyne concinnula possessing anti-angiogenic activity. (April 2021) - Vo, Thanh-Hoa; Lin, Yu-Chi; Liaw, Chia-Ching; Pan, Wen-Pin; Cheng, Jing-Jy; Lee, Ching-Kuo; Kuo, Yao-Haur
Abstract: After anti-angiogenic activity screening, the potential n -butanol layer partitioned from the ethanol extract of Staurogyne concinnula was conducted. Further purification by Diaion HP20 column and preparative HPLC chromatography, four undescribed triterpenoid saponin derivatives, along with the known baptisiasaponin I, and four known phenylpropanoid glycosides were isolated and characterized from n -butanol layer. The structures of isolated compounds were elucidated by ESI-MS, 1D, and 2D MNR data. Biological evaluation revealed that baptisiasaponin I possessed significant anti-angiogenic effects (IC50 4.0 ± 0.2 μM). Further mechanism of action of baptisiasaponin I by inhibition of integrin/FAK/paxillin signaling pathway and its downstream effectors as MMP2 and MMP9 are also presented. Graphical abstract: Image 1 Highlights: A phytochemical and anti-angiogenic investigation of the ethanol extract of Staurogyne concinnula was performed. Four undescribed oleanane-type saponins have been identified. Their anti-angiogenic activity was tested by conducting Matrigel endothelial cell tube formation assays. The isolated baptiasiasaponin I (4 ) was demonstrated to inhibit integrin/FAK/paxillin signaling pathway and its downstream effectors including MMP2 and MMP9.